Disseleneto m-trifluormetil difenila atenua as fases da sensibilização motora comportamental induzidas por morfina em camundongos - Rodrigues, Renata Fritzsche (2022)
m-Trifluoromethyl-diphenyldiselenide (m-CF3-PhSe)2 has multiple targets, including the glutamatergic system and the opioid, in addition to having antioxidant properties. Behavioral locomotor sensitization, characterized by hyperactivity, is a drug addiction and dependence model used experimentally. Several pathways contribute to these aspects, such as the opioid system, dopamine and glutamate receptors modulation. Furthermore, redox imbalance favors this condition. This study aimed to investigate the effect of (m-CF3-PhSe)2 on the acquisition, morphine withdrawal, and drug re-exposure phases on morphine-induced behavioral locomotor sensitization in mice. This study used 30 day-old male Swiss mice (CEUA 5302070619). They were treated with saline or morphine 10 mg/kg twice a day for three days; in the next five days, they were kept abstinent, and received saline or morphine on the ninth day. To assess the compound effect on this protocol, (m-CF3-PhSe)2 was administered during acquisition (first 3 days), on morphine withdrawal or re-exposure (ninth day), soon after the morphine dose on the ninth day, the mice were challenged in the locomotor activity test. Markers of oxidative stress were determined, in addition to protein levels of opioid, dopamine, and glutamate receptors in the mouse cerebral cortex. The results showed that re-exposure to morphine increased the content of opioid (MOR, DOR and KOR) and glutamatergic receptors (NMDA 2A and 2B). However, it decreased the levels of dopamine receptors (D1 and D2), in addition to triggering a redox imbalance, as it increased the levels of reactive species and markers of lipid peroxidation and altered the activity of antioxidant enzymes. In conclusion, (m-CF3-PhSe)2 attenuated morphine-induced locomotor sensitization and protected against biochemical and molecular alterations caused by re-exposure to morphine in mice.